Impact of Body Mass Index on Immunogenicity of Pandemic H1N1 Vaccine in Children and Adults - Callahan, S. Todd (J Infect Dis, 2014)
Obesity emerged as a risk factor for morbidity and mortality related to 2009 pandemic influenza A (H1N1) infection. However, few studies examine the immune responses to H1N1 vaccine among children and adults of various body mass indices (BMI). Pooling data from 3 trials of unadjuvanted split-virus H1N1 A/California/07/2009 influenza vaccines, we analyzed serologic responses of participants stratified by BMI grouping. A single vaccine dose produced higher hemagglutination inhibition antibody titers at day 21 in obese compared to nonobese adults, but there were no significant differences in responses to H1N1 vaccine among children or adults of various BMI following 2 doses.